QUEM É O ENFERMEIRO? - Adélia K. Nakatani; Elizabeth Esperidião; Lourdes M. S. Andraus; Jeanne Marie R. Stacciarini (Universidade Federal de Goias, 1999)
WHO IS THE NURSE? We developed a survey study to identify, in a determined group, what the social representation of the nurse is. The research was done in the Nursing Faculty of the Federal University of Goiás (UFG). To collect data we applied a questionnaire to a sample of 28 subjects that were visiting the Faculty at the time (they were attending a continuous education project: "The Community goes to the UFG"). The data analysis was based on the content of the subjects descriptions, trying to determine their meaning. The most frequent representations were "doctors assistant", "someone who works with illness", "moral demand", "charitable job", "social recognition" and others.